Vacuum Phenomenon of the Sacroiliac Joint: Correlation with Sacropelvic Morphology - Takata, Yoichiro (Asian Spine J, 2016)
STUDY DESIGN: A radiologic study of sacropelvic morphology and vacuum phenomenon of sacroiliac joint in subjects unrelated to low back pain. PURPOSE: The aim of this study is to describe the relationship between sacropelvic morphology and vacuum phenomenon of the sacroiliac joint. OVERVIEW OF LITERATURE: Lumbopelvic alignment and sacropelvic morphology are associated with the pathomechanisms of various spinal disorders. The vacuum phenomena of the sacroiliac joint (SJVP) are often observed in clinical practice, but the relationships between these phenomena and sacropelvic morphology have not been investigated. This study examined the prevalence of SJVP in computed tomography (CT) images and the relationship between sacropelvic morphology and SJVP. METHODS: We analyzed multiplanar CT images of 93 subjects (59 men, 34 women). Pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and lumbar lordosis (LL) were measured using the three-dimensional reconstruction method. The prevalence of SJVP in multiplanar CT images were reviewed. Roland-Morris Disability Questionnaire (RDQ) scores and the modified Japanese Orthopedic Association (JOA) score, which focuses on subjective symptoms and restriction of activities of daily living, were also obtained from all the subjects. RESULTS: Thirty-six of the 93 subjects had SJVP (39%), with marked female predominance (91% women, 8.5% men). Men with SJVP had significantly lower PI than men without SJVP (35.1° vs. 46.3°, p<0.05). There was no correlation between SJVP and the modified JOA or RDQ scores. CONCLUSIONS: These data suggest that differences in sacropelvic morphology can influence the biomechanical environment and contribute to SJVP in men. Presence of SJVP did not affect JOA or RDQ scores.